Redescription of five gnathiid species from Japan (Crustacea: Isopoda) - Ota, Yuzo (Zootaxa, 2013)
Five gnathiid species from Japan are redescribed based on14 holotypes, their paratypes, topotypes, and new materials. Observations of these specimens revealed that Caecognathia kikuchii (Nunomura, 1992) should be transferred to genus Elaphognathia and Caecognathia nasuta (Nunomura, 1992) to genus Gnathia. Furthermore, Caecognathia amakusaensis Nunomura, 1992, C. saikaiensis Nunomura, 1992, Gnathia azumai Nunomura, 2012a, G. quadricephala Nunomura, 2012a, and G. recticornata Nunomura, 2012a are considered to be junior synonyms of E. kikuchii. Gnathia hirayamai Nunomura, 1992, G. nagasakiensis Nunomura, 2012a, G. shijikiensis Nunomura, 2012a, and G. brevicephala Nunomura, 2012a are considered to be junior synonyms of G. nasuta. Moreover, Gnathia sanrikuensis Nunomura, 1998 and G. mutsuensis Nunomura, 2004 are redescribed. Gnathia bungoensis Nunomura, 1982 is not completely redescribed because the key characteristics were lacking. The geographical records of these species are provided.